"Soft" information management technology adoption in uruguayan dairy: a study case in Florida, Uruguay: 2° part - Álvarez, J. (Agrociencia Uruguay, 2004)
A study involving 61 Uruguayan dairy farmers located in florida was done to improve the understanding about factors, which may promote farm information management software use. Results showed that the same factors found in previous studies also affect Uruguayan dairy farmers behaviour about software use. Among these known factors, both farm size and farmer formal education were relevant. At the same time, the study also allowed to identify other factor affecting software use (not previously reported in the literature), such as farmer's personality variables, learning styles, and goals. Factor analysis showed complex relationships among the explanatory variables. In deciding software use it should be considered not only structural factors, such as farm size, but also additional software user's characteristics, such as learning styles. This knowledge may help making better decisions for both farmer and their advisers, and consequently more successful farm information management.